In-vitro efficacy of Arachis hypogaea (Peanut) peels extract against Haemonchus contortus - TAHIR, A.; AKHTAR, R.; LATEEF, M.; SATTAR, F.; HAFEEZ, M.A.; OMER, M.O.; ZAHID, B.; JAVED, A. (Journal of the Hellenic Veterinary Medical Society, 2020)
Synthetic anthelmintics are becoming ineffective due to development of parasitic resistance. For this reason, traditional medicinal plants are being explored for their anthelmintic potential. The aim of this study was to evaluate the in-vitro anthelmintic activity of Arachis hypogaea L. (peanut) peels against Haemonchus contortus. To assess the anthelmintic effect of Arachis hypogaea L. on 3 life cycles of Haemonchus contortus, egg hatch assay (EHA), larval developmental assay (LDA) and adult motility assay (AMA) were conducted. In these tests, methanol and n-hexane extracts of the plant were used in three concentrations of 10, 15 and 20 mg/ml. Levamisole and PBS were used as positive and negative control groups respectively. Results of these tests showed that methanol extract of Arachis hypogaea L. had higher anthelmintic effect than that of n-hexane extract. Overall both extracts exhibited a significant (p<0.05) dose and a time dependent anthelmintic effect. At 20 mg/ml, methanol extract and n-hexane extract showed 87% and 80% egg hatching inhibition respectively. Methanol and n-hexane extracts at 20 mg/ml showed 83.3% and 76.6% larval mortality respectively. Adult motility test with both extracts showed maximum immobilization of worms after 6 hours of treatment at 20 mg/ml concentration. It is concluded that peels of Arachis hypogaea possess significant anthelmintic potential against nematodes. It may be suggested that the plant can be used further to investigate the in-vivo activity.